Case Report: Report of Infective Endocarditis Caused by Abiotrophia defectiva and Literature Review - Yanqiang Du; Zhan Zhang; Chao Chen; Han Xia; Hua Zhang; Zhangyan Guo; Yi Wang (Frontiers Media S.A., 2022)
ObjectiveTo report the clinical features of the first child with infective endocarditis (IE) caused by Abiotrophia defectiva in mainland China and to raise awareness of the disease.MethodsThe clinical data of a child with IE caused by A. defectiva admitted to Xi'an Children's Hospital in July 2021 were collected, and the relevant literature was reviewed.ResultsThe child was a female, 8 years old, admitted with fever for 4 days and right-sided limb weakness for 3 days. The illness started with suppurative tonsillitis, followed by headache, fatigue, right-sided mouth, slurred speech, right limb weakness, and unstable holding. Transthoracic echocardiography showed that the mitral valve vegetation was formed and vegetation could also be seen at the entrance of the pulmonary vein at the posterior wall of the left atrium. Cranial contrast-enhanced MRI + magnetic resonance angiography showed multiple intracranial pseudoaneurysm formation and pontine infarction. After A. defectiva was detected by metagenomic next-generation sequencing (mNGS) in cerebrospinal fluid and blood detected, the infection was controlled by anti-infective treatment with meropenem and vancomycin. On the 36th day after admission, due to severe headache and slurred speech, the head CT showed hemorrhage of right parietal pseudoaneurysm and cerebral sickle hernia, and right temporo-occipital hematoma evacuation, cerebrovascular malformation resection, and cranial decompression were performed immediately. After the surgery, her speech ability gradually recovered, the muscle strength of her left upper limb was about grade III, while the muscle strength of the rest of the limbs was normal. After a total of 60 days of hospitalization, her family requested to be discharged.ConclusionThis pediatric patient is the first case of childhood IE caused by A. defectiva in mainland China, and the first time in the world that A. defectiva was detected by mNGS in patients with IE.